PENGARUH ELEMEN EKUITAS MEREK TERHADAP LOYALITAS KONSUMEN PADA PRODUK HANDPHONE ANDROID MEREK SAMSUNG DI SEMARANG (Studi pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang) - Safri Nazala, 0725020027 (Students Journal of Economic and Management, 2015)
The purpose of this study was to analyze the influence of brand awareness (brand awareness), perceived quality (perceived quality), brand association (brand association), and brand loyalty (brand loyalty) on consumer loyalty on Andoid phone brand Samsung products. The population in this study were students of the Faculty of Economics, University of Semarang Unisbank using Andoid phone brand Samsung. The samples in this study using purposive sampling, the sampling technique with a specific purpose. The analysis tool used is multiple linear regression analysis.Â  The results of the analysis can be concluded that: brand awareness positive effect on customer loyalty. Brand associations positive effect on customer loyalty. Perceived quality has positive influence on customer loyalty. Brand loyalty positive effect on customer loyalty Keywords:Â  brand awareness, perceived quality, brand association, brand loyalty and customer loyalty